Optimizing Digital-Based Learning to Improve Alpha Generation Psychomotor Skills - Eimirilleikbeiraney, Eimirilleikbeiraney; Herpratiwi, Herpratiwi; Rosidin, Undang; Firdaus, Rangga (UNDIKMA, 2024)
Teachers are the main component in the learning process at school that determines the success of their students. The learning process occurs when interaction between teachers and students or vice versa is produced by changes in behavior in the form of new knowledge, strengthening insight and experience. The utilization of digital media in learning is required to be able to have an impact on the development of the alpha generation who are most familiar with the internet of all time. this research uses the literarure review method to thoroughly explore the effect of digital game-based learning media to improve the psychomotor abilities of the alpha generation. There are 10 journals used by researchers, most of the studies were conducted in Indonesia. The results of the research on the use of digital technology in learning have opened up new opportunities to improve interactivity, engagement and learning effectiveness. Alpha generation, born in the era of advanced digital technology, has high adaptability to technology. This allows them to more easily adapt to digital-based learning.